Роль соціокультурних чинників у процесі самовизначення територіальних співтовариств як соціокультурних систем - Чемшит, Олександр Олександрович; Ємельянова, Юлія Павлівна; Chemshyt, Oleksandr O.; Yemelianova, Yuliia P. (Національний університет "Юридична академія України імені Ярослава Мудрого", 2011)
Аналізується роль соціокультурних чинників у процесі соціально-політичного самовизначення територіальних співтовариств та розробки стратегії їх геополітичного розвитку.

The social-cultural factors and their role in the social-political self-determination of the territorial communities as social-cultural systems are analyzed in this article. The author believes that it is essential to make a culturologycal examination of any new social-political and geopolitical projects prior to their commence
Role of sociocultural factors in the determination process of territorial communities as a sociocultural systems
Keywords: реальність соціальна; територіальні співтовариства; система соціокультурна; природне середовище; несвідоме мотиваційне поле; інтенция до соціального; проект самовизначення; Social reality; territorial community; social-cultural system; environment; subconscious motivation; intention to sociality; self-determination project